Effectiveness of Hidden Word Game to Improve Ninth Graders’ Vocabulary Mastery - Jedo, Merhtildis Selviana (International Journal of English Education and Linguistics (IJoEEL), 2025)
This research aims to examine the effectiveness of using the hidden word game in improving the English vocabulary mastery of ninth-grade students at Susila Koting junior high school. The background of this research is the low vocabulary mastery among students, influenced by a lack of variation and interactivity in teaching approaches. The use of engaging learning media, such as games, is expected to increase students’ learning motivation and enhance their language skills. This research employs a quantitative method with a quasi-experimental design, where class IXA serves as the control group (without the hidden word treatment) and class IXB as the experimental group (with the hidden word treatment), each consisting of 20 students. Data collection was carried out through tests (pre-test and post-test), and the data were analyzed using inferential statistical tests with the help of SPSS software version 30. The results of the research show that the test instruments used are valid and reliable. The pre-test and post-test data from the experimental class demonstrate a significant improvement in vocabulary mastery. The normality and homogeneity tests indicate that the data are normally distributed and homogeneous. The results of the paired sample t-test and independent sample t-test reveal a significant difference between the experimental and control groups. The effectiveness test using Cohen’s d produced a very large value, indicating that the use of the hidden word game has a very strong influence on improving students' vocabulary mastery.